1992
DOI: 10.1002/bit.260400909
|View full text |Cite
|
Sign up to set email alerts
|

Development of a single‐pass ceramic matrix bioreactor for large‐scale mammalian cell culture

Abstract: A single-pass, plug-flow bioreactor has been developed in which oxygen is supplied to entrapped hybridoma cells via silicone tubes threaded through the square channels of a macroporous ceramic monolith. Oxygen diffuses from the gas phase, through the silicone tubing, across the open square channel, and into the pores of the ceramic wall where it is consumed by entrapped cells. Advantages of such a reactor include higher product yields, protection of cells from detrimental hydrodynamic effects, no internal movi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The bioreactors were constructed using ceramic monolith structures obtained from Corning Inc. (Corning, NY). The monoliths, described in detail by Applegate (1991), were composed of cordierite and were arranged with open square channels (1.5 mm width, 31 channels/cm 2 ) separated by macroporous ceramic walls (340 µm wall thickness, 20-22 µm mean pore size, 50% porosity). Other physical properties of note are the total pore volume (0.54 cm 3 /g of ceramic) and the bulk density (1.07 g/cm 3 ) of the monoliths.…”
Section: Sample Preparation For Radioimmunoassay (Ria)mentioning
confidence: 99%
See 2 more Smart Citations
“…The bioreactors were constructed using ceramic monolith structures obtained from Corning Inc. (Corning, NY). The monoliths, described in detail by Applegate (1991), were composed of cordierite and were arranged with open square channels (1.5 mm width, 31 channels/cm 2 ) separated by macroporous ceramic walls (340 µm wall thickness, 20-22 µm mean pore size, 50% porosity). Other physical properties of note are the total pore volume (0.54 cm 3 /g of ceramic) and the bulk density (1.07 g/cm 3 ) of the monoliths.…”
Section: Sample Preparation For Radioimmunoassay (Ria)mentioning
confidence: 99%
“…Other physical properties of note are the total pore volume (0.54 cm 3 /g of ceramic) and the bulk density (1.07 g/cm 3 ) of the monoliths. The material was pretreated for biocompatibility by boiling with 10% nitric acid and rinsing with deionized water and PBS as described by Applegate (1991). Preliminary experiments demonstrated that TC-3 cells grew in the pores and channels of this material and that they remained responsive to secretagogue stimulus.…”
Section: Sample Preparation For Radioimmunoassay (Ria)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although several novel continuous bioreactors have been developed for the culture of suspended mammalian cells (1)(2)(3)(4)(5)(6)(7)(8)(9), conventional roller bottles still provide the simplest means for culturing suspended mammalian cells that are shearsensitive but still require some means of agitation for cell suspension and oxygen and nutrient dispersion. Although each novel bioreactor has its own advantages, such as improvements in cell density, viability percentages, monoclonal antibody secretion rates, etc., these systems are generally not as mechanically simple or as easily scaleable as are roller bottles, require special user training, and require capital investment.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous supply of medium coupled with continuous or intermittent cell or product harvest should result in a longer production phase and more efficient use of cells and medium. For these reasons, current research has focused on innovative continuous reactors such as the NASA microgravity bioreactor (7), hollow fiber reactors (8, 9), a single‐pass, plug flow reactor (10), a depth filter perfusion system (11), and spin‐filter bioreactors (12, 13). Despite continuing advances in cell culture apparatus technology, roller bottles are still prevalent throughout the industry because of their simplicity and relative effectiveness.…”
Section: Introductionmentioning
confidence: 99%